Research development about digital resilience: A Scoping Review - Fauziah Saputri, Intan Nur; Solichah, Novia; Wahyu, Siva Ananda; Zam Ani, Ahmad Faisal; Firda Aprasanjani, Baiq Ashri; Masykuroh, Ummi Farichatul (Journal of Indonesian Psychological Science (JIPS), 2024)
ABSTRACT The increased use of technology from 2022 to early 2024 has had a significant impact, including an increase in issues such as cyberbullying, cybercrime, phishing, and the impact on mental health. Digital resilience is the focus of research as a potential solution. The method in this study is in the form of scooping reviews from the past which are prioritized in the search for data related to problems published in the last 24 years. The last year, 2001 – 2024. There were 82 scientific articles that included qualitative and quantitative journals, but we identified 14 studies that met the search and eligibility criteria in the international journals we found. These findings show that there are benefits to the implementation of digital resilience in dealing with the negative influence of digital technology. The results of this analysis show that the important role of digital resilience for every individual, especially adolescents, can be used as a reference as a solution to deal with the negative influence of cyber bullying and the negative impact of social media. KEY WORDS: digital resilience; youth; scoping review ABSTRAK Peningkatan penggunaan teknologi dari 2022 hingga awal 2024 memiliki dampak signifikan, termasuk peningkatan masalah seperti cyberbullying, cybercrime, phishing, dan dampak pada kesehatan mental. Digital resilience menjadi fokus penelitian sebagai solusi potensial. Metode dalam penelitian ini berupa scooping review dari terdahulu yang diprioritaskan dalam pencarian data terkait problematika yang diterbitkan dalam 24 tahun terakhir. Tahun terakhir, 2001 – 2024. Terdapat 82 artikel ilmiah yang termasuk jurnal kualitatif dan kuantitatif, akan tetapi kami mengidentifikasi terdapat 14 studi yang memenuhi kriteria pencarian dan kelayakan pada jurnal internasional yang kami temukan.Temuan ini menunjukkan bahwa adanya manfaat implementasi dari digital resilience dalam menghadapi pengaruh negatif dari teknologi digital. Hasil analisis ini menunjukkan bahwa peran penting digital resilience bagi setiap individu khususnya remaja yang dapat dijadikan rujukan sebagai solusi menghadapi pengaruh negatif cyber bullying dan dampak negatif media sosial. KATA KUNCI digital resilience; youth; scoping review